(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Cooperative behavior is defined as the interaction of individuals in an interdependent or dependent way to obtain reinforcements, relating to the survival of the species in obtaining and maintaining scarce resources. This study consisted of a systematic review of experimental and theoretical studies of cooperation indexed in twelve Behavior Analysis (BA) journals in the years 2017-2021, using the descriptor “cooperation” in 114 articles published in Portuguese, English, and Spanish. The analyzes investigated the functional definition used to describe cooperation, its critical variables and the methodology employed. Data obtained show consistency between authors, regarding the functional definition of cooperation in the 17 articles included, with emphasis on interdependence, mutual reinforcement, and coordination. The internal consistency in BA regarding the concept contributes to interdisciplinary dialogues, the study of social behavior, cultural practices, the development of a behavioral-analytic research agenda, and the advancement of sciences focused on cooperative research.